LIFE HISTORY OF A MAJOR CARP HYBRID ROHU-CATLA - Reddy, P Konda; Varghese, T J (Indian Journal of Fisheries, 2011)
A hybrid, rohu-catla, was produced by crossing male rohu with femalecatla. The embryonic and larval developments of this hybrid, when compared withthose of rohu and catla, showed that the development of the hybrid is normal, withoutany deformities, and is more or less similar to that of the parental species. Theperiod of incubation in the hybrid was 15 h 42 min., as against 16 h 40 min. incatla and 15 h 30 min. in rohu. The hybrid exhibited intermediate characters inrespect of the position of mouth and the nature of lips. The caudal spot in thehybrid was triangular as in catla, but more prominent. The alimentary canal intwo-day-old larvae of the hybrid was filled with algae and cladocerans, indicatingthat feeding had commenced on the second day itself, with yolksac still present.